A PLAGIARISM AMONG UNIVERSITY STUDENTS - Amanda, Yulia; Saddiah, Halimatun; Auliandhy Parinduri, Muhammad Rasya (CV. Asry Persada Quality, 2025)
Plagiarism is an ethical violation in academia that still frequently occurs in higher education environments. Students, as the main subjects in the learning process, are expected to have academic integrity; however, many are involved in plagiarism. This study aims to analyze the causes and impacts of plagiarism among students and to provide preventive solutions that can be implemented by educational institutions. The method used in this research is a literature study with a descriptive qualitative approach. The findings indicate that a lack of understanding of academic ethics, academic pressure, and the development of information technology are the main causes of plagiarism. The impacts include damage to the reputation of individuals and institutions, a decline in the quality of graduates, and hindered advancement of knowledge. Addressing plagiarism requires collaboration between students, lecturers, and institutions through educational and regulatory approaches